Evaluation of Lip Profile in Adolescent Subjects with Skeletal Class I Occlusion and Class III Malocclusion - Manar Y Abdul-Qadir; Saba H Al-Zubaidy; Ra'ed J Sa'eed (University of Mosul, College of Dentistry, 2012)
Aims: To examine the difference of anteroposterior lip position using lateral cephalometric radiograph in a sample of Class I and Class III malocclusion adolescents. Materials and Methods: The study comprised 80 adolescent subjects (40 males and 40 females) who were divided according to the type of occlusion into two groups; dental and skeletal Class I group (40 subjects) and the dental and skeletal Class III group (40 subjects). On lateral cephalometric radiograph, lip position was assessed using 7 linear and 2 angular measurements. The data were analyzed using independent samples t-test. Results: Significant differences were noticed between the two groups for most of the variables. The combined sample showed more retrusive position of the upper lip in Class III group in relation to Steiner, Burtone and Canuts lines. While significantly more retrusive position of the lower lip in Class III group was noticed in relation to Burstone and Harmony lines. In addition, Class III sample showed a significantly smaller H angle and greater Z angle than Class I group. When these reference lines were compared for sensitivity, H line and B line were found to have the greatest power to differentiate between the 2 groups. Sexual dimorphism was noticed in both groups. In Class I group, males showed more protru-sive lips in relation to Steiner line. While in the Class III lines group, males showed more protrusive upper lip in relation to Burton and Canuts lines and in both groups males showed significantly larger H angle and smaller Z angle than females. Conclusions: The skeletal Class III malocclusion tend to have lip profile that differs significantly from skeletal Class I occlusion and is characterized by retrusive upper lip, protrusive lower lip, smaller H angle and more obtuse Z angle. These findings emphasize the importance of integumental evaluation as an aid in orthodontic diagnosis and treatment planning of this type of malocclusion.